MANIFESTATION OF BRONCHIAL REACTIVITY IN THE WORKERS EXPOSED TO VARIOUS GASES AT THE GASIFICATION DEPARTMENT OF THE POWER PLANTS OF KOSOVO - ISLAMI, PELLUMB; BOZALIJA, ADNAN; ISLAMI, HILMI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study aimed to determine the effects of indoor air pollution on workers and the effects of discharged gases, such as CO, CO2, NO2, O3, SO2, NH3, and PM, on the manifestation of bronchial reactivity during the process of gasification at the power plants in Kastriot, Kosovo. Methods: Parameters of lung function were determined using body plethysmography. Airway resistance (Raw) and intrathoracic gas volume (ITGV) were measured; based on these values, specific airway resistance (SRaw) and specific airway conductance were calculated. Results: The study was performed in two groups: the control group and the experimental group. The control group consisted of 32 healthy people, whereas the experimental group consisted of 55 workers of the gasification department of the power plants in Kastriot, Kosovo. The results of this study indicated that the mean value of SRaw significantly increased in the experimental group (p<0.05) compared to the control group (p>0.1). This study also showed that smoking is in favor of the negative effects of air pollution at the premises of the gasification department (p<0.01). Measurements of the respiratory systems were made before and following provocation with histamine–aerosol (1 mg/ml) in the control and experimental groups. Changes between these two groups following this provocation with histamine–aerosol were found to be statistically significant (p<0.01). Conclusion: Although air pollution requires time to cause a respiratory pathology, it permanently affects the manifestation of bronchial reactivity. This finding suggests that the real situation of these workers exposed to air pollution during the process of gasification poses a serious risk to their health and particularly to normal respiratory function.